Ferroelectric BaTiO3@ZnO heterostructure nanofibers with enhanced pyroelectrically-driven-catalysis. Issue 1 (January 2019) - Wang, Lang; Haugen, Neale O.; Wu, Zheng; Shu, Xiaoxin; Jia, Yanmin; Ma, Jiangping; Yu, Shigang; Li, Huamei; Chai, Qunxia
Abstract: In this work, an obvious enhancement of pyroelectrically-driven catalytic activity is found in BaTiO3 @ZnO heterostructures synthesized hydrothermally and then calcined. The pure BaTiO3 is able to decompose up to 45% of the RhB dye in aqueous solution (5 mg/L) under 30–54 °C cold-hot cycle. As the ZnO content coating on the surface of the BaTiO3 nanofibers is increased from 0 to 5 wt%, the decomposition ratio of the BaTiO3 @ZnO heterostructures for RhB dye in aqueous solution first increases and then decreases, giving a maximum value of 97% at 2.5 wt%. The kinetic rate constant ( K = 0.06384 cycle −1 ) of the catalytic reaction for BaTiO3 @2.5%ZnO is 4 times higher than that of pure BaTiO3 . The enhancement of catalytic activity of BaTiO3 @ZnO may be due to the formation of a semiconductor junction in which the electric field effectively separating the pyro-induced electron-hole pairs and further accelerates carrier migration. The ferroelectric heterostructures of BaTiO3 @ZnO show pyroelectrically-driven-catalysis and may hold potential for use in decomposing dye wastewater through harvesting cold-hot alternation thermal-energy.